2019
DOI: 10.1186/s12962-019-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for one quality-adjusted life year in Iran

Abstract: Background Recent years have witnessed a strong tendency to apply economic evidence as a guide for making health resource allocation decisions, especially those related to reimbursement policies. One such measure is the use of the cost-effectiveness threshold as a benchmark. This study explored the threshold for use in the health system of Iran by determining society’s preferences. Methods A cross-sectional household survey based on the contingent valuation method was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 25 publications
3
25
3
5
Order By: Relevance
“…The amount that the participants were willing to pay for the additional QALY gained from the life-saving treatment for a family member was about US$ 1,355, which represent 0.27 of the GDP per capita. These values are slightly lower than the WTP values of 0.22 to 0.56, and 0.57 of the GDP per capita for the additional QALY gained ndings reported from studies in Iran (2,30). Comparatively speaking other countries such as Thailand found the WTP value of 1.42 times the GDP per capita for the additional QALY gained from life-saving interventions (4).…”
Section: Discussionmentioning
confidence: 61%
“…The amount that the participants were willing to pay for the additional QALY gained from the life-saving treatment for a family member was about US$ 1,355, which represent 0.27 of the GDP per capita. These values are slightly lower than the WTP values of 0.22 to 0.56, and 0.57 of the GDP per capita for the additional QALY gained ndings reported from studies in Iran (2,30). Comparatively speaking other countries such as Thailand found the WTP value of 1.42 times the GDP per capita for the additional QALY gained from life-saving interventions (4).…”
Section: Discussionmentioning
confidence: 61%
“…The amount that the participants were WTP for the additional QALY gained from the life-saving treatment for a family member was about US$ 1,355, which is about 0.27 of the GDP per capita. These values are slightly lower than the WTP values of 0.22 to 0.56, and 0.57 of the GDP per capita for the additional QALY gained ndings reported from studies in Iran (2,29). However, others from Thailand found the WTP value of 1.42 times the GDP per capita for the additional QALY gained from life-saving interventions (4).…”
Section: Discussionmentioning
confidence: 62%
“…However, a study in Tehran reported an average WTP per QALY of the participants ranging from US$ 1,032 to US$ 2,666. These minimum and maximum values accounted for 0.22 to 0.56 GDP per capita of Iran in 2014 (2).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The scarcity of healthcare resources and the increasing clients' treatment demands challenge the decisions on resource allocation including financial reimbursements, especially in the health systems of the resource-constrained countries (1,2). The cost-effectiveness analysis which compares the costs and health gains from two or more alternative interventions in terms of the incremental cost-effectiveness ratio (ICER), is widely used to handle such challenging decisions (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%